How Canadians Communicate V: Sports - Edited by David Taras and Christopher Waddell (Athabasca University Press, 2016)
Fewer Canadians than ever are lacing up skates, swimming lengths at the pool, practicing their curve ball, and experiencing the thrill of competition. However, despite a decline in active participation, Canadians spend enormous amounts of time and money on sports, as fans and followers of sporting events and sports culture. Never has media coverage of sports been more exhaustive, and never has it been more driven by commercial interests and the need to fuel consumerism, on which corporate profits depend. The power plays now occurring in the arena of sports are by no means solely a matter of money, however. At issue as well in the media capture of sports are the values that inform our daily lives, the physical and emotional health of the population, and the symbols so long central to a sense of Canadian identity. Writing from a variety of perspectives, the contributors to this collection set out to explore the impact of the media on our reception of, and attitudes toward, sports-to unpack the meanings that sports have for us as citizens and consumers. Well-known hockey writer Roy MacGregor delves into the influence of big media and big sports on the practice of objective journalism; Richard Gruneau examines the worrisome relationship between sports participation and socioeconomic class; blogger Derrick Newman investigates the impact of fantasy leagues on sports coverage; sociologist Harry Hiller looks at the iconic dimensions of the Vancouver Olympics. Other contributors shed light on the way in which the media serve to transform sports-including, of course, hockey-into a vehicle for the expression of identity and nationalism. Still others probe the function of sports as spectacle: the escalation of violence, controversies over drug use, and the media's coverage of tragic deaths. The goal is not to score points but to prompt critical discussion of why sports matter in Canadian life and culture and how they contribute to the construction of Canadian identity.